Maternity care professionals' preparedness for and experiences of screening and responding to disclosures of domestic violence in the peripartum period: A protocol for a qualitative evidence synthesis - O'Shea, Laura; Daly, Deirdre; Corbally, Melissa (My University, 2025)
Maternity care professionals, such as midwives, public health nurses, doctors, and social workers, are in the unique position of having regular contact with women in the peripartum period. They are well-placed to recognise and respond to disclosures of domestic violence, however many lack confidence and feel unprepared for this in practice. While there are screening tools used for enquiry about domestic violence in pregnancy, there are variations in the tools used, the frequency and timing of enquiry, and the response/referral pathways across professions. Research exists on the role of health care professionals such as midwives, doctors, and nurses with regards to domestic violence, however little is understood about the collective and shared experience of maternity care professionals who screen for and respond to domestic violence in the peripartum period.
PUBLISHED
Keywords: Gender issues, gender studies; Maternity Care; Midwifery